THE INFLUENCE OF E-SERVICE QUALITY ON CONTINUANCE INTENTION MEDIATED BY CUSTOMER TRUST AND CUSTOMER SATISFACTION IN THE USAGE OF MOBILE HEALTH APPLICATION - Satria, Anitha Soleha; Kurniawati, Kurniawati (Studies and Scientific Researches. Economics Edition, 2023)
This study aims to analyze the effect of e-service quality on continuance intention which is mediated by customer trust and customer satisfaction on mobile health applications user. Methods of data collection techniques using non- probability sampling with the purposive sampling method. Data were collected from 280 respondents with the criteria of mobile health application users in Indonesia. Questionnaires were distributed via Google form and consisted of 28 statements which were answered based on five Likert scales. The analytical method used in this study is Structural Equation Model (SEM). The results showed that e-service quality has a positive effect on continuance intention, e- service quality has a positive effect on customer trust, customer trust has a positive effect on continuance intention, and e-service quality has a positive effect on continuance intention mediated by customer trust partially. In addition, customer trust has a positive effect on customer satisfaction. However, electronic service quality does not have a positive effect on customer satisfaction, customer satisfaction also does not have a positive effect on continuance intentions, and customer satisfaction does not have a mediating effect between electronic service quality on continuance intentions. This research is used as evaluation material for mobile health applications to improve e-service quality to shape customer trust and customer satisfaction and gain user continuance intention for using mobile health application.